2016
DOI: 10.1038/mt.2015.195
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Cell Priming Enhances Transfection Outcomes in Adult Human Mesenchymal Stem Cells

Abstract: Human mesenchymal stem cells (hMSCs) are one of the most widely researched stem cell types with broad applications from basic research to therapeutics, the majority of which require introduction of exogenous DNA. However, safety and scalability issues hinder viral delivery, while poor efficiency hinders nonviral gene delivery, particularly to hMSCs. Here, we present the use of a pharmacologic agent (glucocorticoid) to overcome barriers to hMSC DNA transfer to enhance transfection using three common nonviral ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(68 citation statements)
references
References 49 publications
10
58
0
Order By: Relevance
“…Plasmids Bernasconi et al, 1997;Braun et al, 1999;Chen et al, 2011;Choi & Lee, 2005;Jain et al, 1999;Koster et al, 2002;Köster et al, 2006;Lin et al, 2003;Nair et al, 2002) compared to those seen here in hMSCs. Our results showing increased transgenic enzyme activity in addition to increased transgenic protein production (all relative to VCs) are probably not specific to only luciferase transgenes because we previously reported DEX-priming yielded 4-7-fold increases in transgenic β-galactosidase enzyme activity, whereas also increasing transgenic EGFP mean fluorescence intensity by about two-fold, all relative to VC (Kelly et al, 2016). Our results showing increased transgenic enzyme activity in addition to increased transgenic protein production (all relative to VCs) are probably not specific to only luciferase transgenes because we previously reported DEX-priming yielded 4-7-fold increases in transgenic β-galactosidase enzyme activity, whereas also increasing transgenic EGFP mean fluorescence intensity by about two-fold, all relative to VC (Kelly et al, 2016).…”
Section: Enhancement By Dex Is Pdna Sequence Element Independentmentioning
confidence: 48%
See 4 more Smart Citations
“…Plasmids Bernasconi et al, 1997;Braun et al, 1999;Chen et al, 2011;Choi & Lee, 2005;Jain et al, 1999;Koster et al, 2002;Köster et al, 2006;Lin et al, 2003;Nair et al, 2002) compared to those seen here in hMSCs. Our results showing increased transgenic enzyme activity in addition to increased transgenic protein production (all relative to VCs) are probably not specific to only luciferase transgenes because we previously reported DEX-priming yielded 4-7-fold increases in transgenic β-galactosidase enzyme activity, whereas also increasing transgenic EGFP mean fluorescence intensity by about two-fold, all relative to VC (Kelly et al, 2016). Our results showing increased transgenic enzyme activity in addition to increased transgenic protein production (all relative to VCs) are probably not specific to only luciferase transgenes because we previously reported DEX-priming yielded 4-7-fold increases in transgenic β-galactosidase enzyme activity, whereas also increasing transgenic EGFP mean fluorescence intensity by about two-fold, all relative to VC (Kelly et al, 2016).…”
Section: Enhancement By Dex Is Pdna Sequence Element Independentmentioning
confidence: 48%
“…Although DEX increased transgenic luciferase activity normalized to total protein by about 10-fold in transfected hMSCs, DEX only increased the amount of transgenic luciferase protein by about two-fold, as quantified by western blot analysis normalized to total protein (Figure 1c,d), suggesting that DEX-priming somehow increases transgenic enzyme activity downstream of transgenic protein synthesis. It is likely that hMSC transfection could be primed with many other Gc drugs in addition to DEX, as our previous work demonstrated that priming with cortisol similarly resulted in significant enhancement of transgene expression in transfected hMSCs (Kelly et al, 2016). It is likely that hMSC transfection could be primed with many other Gc drugs in addition to DEX, as our previous work demonstrated that priming with cortisol similarly resulted in significant enhancement of transgene expression in transfected hMSCs (Kelly et al, 2016).…”
Section: Enhancement By Dex Is Pdna Sequence Element Independentmentioning
confidence: 88%
See 3 more Smart Citations